(untitled) (Acta Scientiarum. Agronomy, 2016)
The aim of this study was to assess alternatives for viable corn storage for small rural properties in two annual storage experiments. A 4Ã—5 factorial design was used with four types of storage (conventional bags, hermetic bags, metal silos and corncobs) and five periods of storage (0, 3, 6, 9 and 12 months). We used corn hybrids 2B688RR and 30K73Hx cultivated in winter 2012 and summer 2012/2013 in the city of Dois Vizinhos, Paraná, Brazil. The moisture contents, counts of Aspergillus sp. and Fusarium sp., and the occurrence of aflatoxins (B1, B2, G1 and G2) were assessed. The kernels stored in hermetic bags had lower moisture contents. Aspergillus sp. and Fusarium sp. were observed in 20.37 and 86.11% of winter storage samples, respectively, and in 83.3 and 91.6% of summer storage samples, respectively. The storage system and time of storage had no influence on the occurrence of Aspergillus sp. and aflatoxins in the winter crop samples. The corncobs from the summer crop samples had the lowest counts of Aspergillus sp. and did not have aflatoxins. We detected aflatoxins at concentrations of 2.8-14.5 and 3-197.5 µg kg-1 in the winter and summer crop samples, respectively.